Dexamethasone alleviates pemetrexed-induced senescence in Non-Small-Cell Lung Cancer. (September 2018) - Ge, Haiyan; Ke, Jun; Xu, Nuo; Li, Hongqing; Gong, Jin; Li, Xiangyang; Song, Yuanlin; Zhu, Huili; Bai, Chunxue
Abstract: Pemetrexed (PEM) is a novel and multi-targeted antifolate used as an antineoplastic agent for non-small cell lung cancer (NSCLC) and pleural mesothelioma. Although glucocorticoid was often used with PEM to reduce toxicity during the chemotherapy, it is not clear yet whether glucocorticoid co-administration could affect PEM efficacy in NSCLC. Here we established NSCLC cell lines and examined the effects of dexamethasone (DEX) on PEM sensitivity in vitro and in xenograft models. DEX co-administration reduced chemotherapy sensitivity to PEM in xenograft models. DEX co-administration promoted cell growth and weakened senescence growth arrest, such as altered secretions of proinflammatory and mitogenic cytokines, reminiscent of a senescence associate secretory phenotype (SASP). CSCs in DEX co-administration group were subsequently found to be less sensitive towards PEM treatment as measured by cell proliferation and generation of tumor spheres in the presence of PEM. Survival molecule B-cell lymphoma-2 (Bcl-2) may involve in this process and blockage of Bcl-2 could reverse altered senescence and CSCs abilities, thus alleviated PEM insensitivity. As such, DEX might suppress the antitumor activity of PEM through altered SASP level that had induced traits similar to CSCs. Highlights: DEX co-adminstration with PEM in NSCLC promotes cell growth, weakens senescence growth arrest and induces PEM insensitivity. DEX co-adminstration with PEM in NSCLC alters SASP expression. Blockage of survival molecule Bcl-2 reverses altered senescence, SASP expression and CSCs abilities.